Reliability of Escherichia coli and faecal streptococci as indicators of Salmonella in frozen fishery products - Shrivastava, K.P., Gopalakrishna Iyer, T.S. and (Fishery Technology, 2021)
The results obtained in the present study suggest that Escherichia coli and faecal streptococci are of little value as indicators of the possible presence of Salmonella in frozen fishery products.